Entrepreneurship in Medical Education: Evaluation of the Entrepreneurship in Healthcare Seminar Series - Amanda Mac; Hayley McKee; Michael Balas; Aazad Abbas; Aida Ahrari; Pawandeep Sandhu; Dante Morra; Sarah McClennan; Alison Freeland (Journal of Regional Medical Campuses)
Background: Innovation and entrepreneurship are central to healthcare. Physicians are ideally positioned to create sustainable healthcare innovations. However, few medical programs in Canada provide training for students to pursue innovation and entrepreneurship. We created the Entrepreneurship in Healthcare Seminar Series (EHSS), a novel initiative designed to teach medical students about developing innovations and launching entrepreneurial ventures. We evaluated the EHSS based on medical student feedback and suggest future directions.